A Transactions Cost Approach to the Theory of Financial Intermediation - Benston, George J.; Smith, Clifford W. (Journal of Finance, 1976)
George J. Benston, Clifford W. Smith, Jr., A Transactions Cost Approach to the Theory of Financial Intermediation, The Journal of Finance, Vol. 31, No. 2, Papers and Proceedings of the Thirty-Fourth Annual Meeting of the American Finance Association Dallas, Texas December 28-30, 1975 (May, 1976), pp. 215-231